Implementation of the Regional Investment Project of Energy Efficiency Increase of the Enterprise of Belgorod (According to Belvodokanal GUP) - Kulik, Anna Mihailovna; Gerasimova, Natalja Anatoljevna; Bondareva, Yana Yurievna; Kogteva, Anna Nikolaevna; Borzenkova, Nadezhda Sergeevna (International Journal of Energy Economics and Policy, 2017)
The purpose of this study is to monitor the execution of the investment program approved by the state unitary enterprise GUP Belvodokanal for the construction, reconstruction, modernization and development of the centralized water supply systems, sewerage and purification of waste water of the city of Belgorod in the period from 2014 to 2018, as well as the proposals related to the improvement of the investment program. The scientific methods, general scientific principles of dialectical development and system approach are used in this article. The main results: the analysis of the existing problems of Belgorod GUP of Belgorod are presented, the efficiency of the investment under the approved investment program is assessed, the analysis and evaluation of the efficiency of capital investments under the project as well as the risk assessment and the planned specific decline in the introduction of the additional measures to the investment program in the field of water supply, approved by Belvodokanal GUP, are conducted. Keywords: Investment program, investment, capital investment, economic efficiency, energy efficiency, payback period, risks. JEL Classifications: H54, L95, O10